Optimalisasi Pendidikan Karakter Melalui Ekstrakurikuler di SMP Negeri 1 Labuhan Haji Barat Aceh Selatan - Azimah Azimah (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2018)
Character education is an important aspect in improving the quality of human resources. Poor management of human resources will eventually lead to poor quality of education. The study took place at SMPN (junior high school) 1 Labuhan Haji Barat in Aceh Selatan. Data were obtained from the school principal, vice principal of student affairs, head of administration section, teachers, and students. The data were collected by observation, interview, and documentation. In this study, the instrument was the researcher himself to conduct observation, interview, and documentation. The data were then analyzed through these three following stages; reduction, display, and verification. Findings showed that the main types of extracurricular activities were sports, religious studies, culture and arts, and others (scout, flag raisers, and Olympiad). In addition, the extracurricular activities which helped optimize the character education included playing volleyball, performing congregated prayers, handshaking with teachers, praying before and after studying, Friday cleaning day, being discipline, saying dzikir of tawheed tasawuf, 7-minute speech, observing Islamic days, giving advice and guidance, dancing rapa-i geleng, learning dances, scout, and flag raising. Further, the obstacles in optimizing the character education were related to the internal factors, from the within students themselves and the teachers, and also the external factors such as from the other students and the school facilities.